Arsitektur Cetiya Dewi Samudera Singkawang Kalimantan Barat - Puji Sulani (Jurnal Lektur Keagamaan, 2014)
This research is a religious archaeology using contextual interpretative archaeological approach. The purpose of this study was to describe the architecture and utilization of the Dewi Samudera Cetiya Singkawang West Kalimantan. Stage of research conducted by collecting, processing, and analyisis of data using shapes analysis and contextual analysis. The result of this study is that Dewi Samudera Cetiya Singkawang West Kalimantan with three space-type siheyuan built in 1873. The construction of the cetiya is follow general rules of Chinese architectural and feng shui rules. Ornament building patterned fauna, flora, people atau character, symbols geometric motifs objects and natural phenomena. Architecture exist which indicate that the general rule of Chinese architecture, feng shui, and ornamentation of the building is still maintained by the board Dewi Samudera Cetiya Singkawang West Kalimantan. Keywords: Architecture, feng shui, Dewi Samudera Cetiya, Singkawang